Towards an ILO approach to climate change adaptation - Harsdorff, Marek; Lieuw-Kie-Song, Maikel; Tsukamoto, Mito (Geneva, 2011)
"This working paper is the joint effort of the Employment Intensive Investment Programme and the Green Jobs Programme. It explores the implications of climate change, its impacts on the world of work and the need for the work of the International Labour Office to adapt to it. It takes stock of the on-going work and identifies the needs for further development."